Association of Venous Outflow Profiles and Successful Vessel Reperfusion After Thrombectomy. (15th June 2021) - Faizy, Tobias Djamsched; Kabiri, Reza; Christensen, Soren; Mlynash, Michael; Kuraitis, Gabriella; Mader, Marius Marc-Daniel; Albers, Gregory W.; Lansberg, Maarten G.; Fiehler, Jens; Wintermark, Max; Marks, Michael P.; Heit, Jeremy J.
Abstract : Objective: Robust arterial collaterals are associated with successful reperfusion after thrombectomy treatment of acute ischemic stroke due to large vessel occlusion (AIS-LVO). Excellent venous outflow (VO) reflects excellent tissue perfusion and collateral status in patients with AIS-LVO. The goal of this study was to determine whether favorable VO profiles assessed on pretreatment CT angiography (CTA) images correlate with successful vessel reperfusion after thrombectomy in patients with AIS-LVO. Methods: This was a multicenter retrospective cohort study of consecutive patients with AIS-LVO treated by thrombectomy. Baseline CTA was used to assess collateral status (Tan scale) and VO using the Cortical Vein Opacification Score (COVES). Favorable VO was defined as COVES ≥3. Primary outcome was excellent vessel reperfusion status (modified Thrombolysis in Cerebral Infarction 2c/3). Secondary outcome was good functional outcome defined as a score of 0 to 2 on the modified Rankin Scale after 90 days. Results: Five hundred sixty-five patients met the inclusion criteria. Multivariable logistic regression analysis showed that favorable VO (odds ratio [OR] 2.10 [95% confidence interval (CI) 1.39–3.16]; p < 0.001) was associated with excellent vessel reperfusion during thrombectomy, regardless of good CTA collateral status (OR 0.87 [95% CI 0.58–1.34]; p = 0.48). A favorable VO profile (OR 8.9 [95%CI 5.3–14.9]; p < 0.001) and excellent vessel reperfusion status (OR 2.7 [95%CI 1.7–4.4]; p < 0.001) were independently associated with good functional outcome adjusted for age, sex, glucose, tissue plasminogen activator administration, good CTA collateral status, and presentation NIH Stroke Scale score. Conclusion: A favorable VO profile is associated with reperfusion success and good functional outcomes in patients with AIS-LVO treated by endovascular thrombectomy. Classification of Evidence: This study provides Class II evidence that a favorable VO profile is associated with reperfusion success and good functional outcomes in patients with AIS-LVO treated by endovascular thrombectomy.